Effects of calcination temperature and zinc-source concentration on chemical-solution synthesized ZnO nanorods - Kuan Y., Cheong; Hartini, Hussin; Khairul Nizar, Ismail (Electrochemical Society, 2009)
Link to publisher's homepage at http://www.electrochem.org/